Das Zusammenspiel von Raum und Technik bei der Etablierung Erneuerbarer Energien. Transformationen in der Energiewende - Radtke, Jörg (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
This paper examines the effects of the German Energy Transition (“Energiewende”) at the social and par- ticularly at the spatial level. The paper uses a concept of space that acknowledges the role of new technology. The approach differentiates between environmental spaces, spaces of conventional energy production and renewable energy production. Additionally, it addresses the question what happens when renewable energy technology meets space. The analysis addresses three key issues: ● Hybridization: Do technology, individuals and nature form an inseparable unit, which cannot (anymore) be separated? ● Disintegration of counter-spaces: Do renewable ener- gies lead to a disintegration of the clear distinction bet- ween technological spaces and their environment? ● Design of space: Which possibilities of collaboration and participation exist for the local population? Furthermore, the paper investigates socio-spatial landscape outcomes that are affected by technological change. As well equally direct and indirect impacts of technology on human action are separated. Both aspects are important for the implementation of renewable energy in Germany. Wind turbines are installed at specific sites which are connected to a meaning, a use or an identity. Technology affects people in their everyday routines by its visual perception and its non-material value. The paper demonstrates different meanings of space concerning symbols of new technologies in varying con- texts, e.g. the installation of a large number of wind tur- bines shapes landscapes. Theoretical reflections draw on the concept of the inclusion of technology from Bruno La-tour and the determination of ‘Other Spaces’ from Michel Foucault. Practical issues related to the Energy Transition are discussed using case studies on wind energy deploy- ment and grid expansion in Germany as an example. The paper aims at discussing the idea of an increased hybridization of nature and technology due to the grow- ing use of renewable energy. A theoretical framework of socio-technological change of societies is developed to understand the current discourse on the German Energy Transition.